A trillion dollars race—how ChatGPT affects stock prices - Marcin Pietrzak (Future Business Journal)
Abstract This study examines the short-term stock market impact of ChatGPT-related corporate announcements among the universe of the US-listed companies. Using the event study method, it identifies statistically significant abnormal returns for firms referencing ChatGPT in SEC filings between January and May 2023. The findings reveal sectoral differences: the information technology sector consistently benefits, while financials and energy face heightened risks. Firm-specific factors, such as market capitalization, beta, and company age, are associated with the magnitude of market reactions. This research highlights the transformative potential of generative AI on capital markets and offers valuable insights for investors, policymakers, and future technological adoption.